Barkhausen-type noise in the resistance of antiferromagnetic Cr thin films - Tosi, L. (2012)
Fil: Tosi, L. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina